Effects of Sedatives on Sleep Architecture Measured With Odds Ratio Product in Critically Ill Patients. (10th August 2021) - Georgopoulos, Dimitris; Kondili, Eumorfia; Alexopoulou, Christina; Younes, Magdy
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Evaluation of sleep quality in critically ill patients is difficult using conventional scoring criteria. The aim of this study was to examine sleep in critically ill patients with and without light sedation using the odds ratio product, a validated continuous metric of sleep depth (0 = deep sleep; 2.5 = full wakefulness) that does not rely on the features needed for conventional staging. DESIGN: Retrospective study. SETTINGS: A 16-bed medical-surgical ICU. PATIENTS: Twenty-three mechanically ventilated patients who had previously undergone two nocturnal sleep studies, one without and one with sedation (propofol, n = 12; dexmedetomidine, n = 11). INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Sleep architecture was evaluated with odds ratio product analysis by the distribution of 30-second epochs with different odds ratio product values. Electroencephalogram spectral patterns and frequency of wake intrusions (3-s odds ratio product > 1.75) were measured at different odds ratio product levels. Thirty-seven normal sleepers were used as controls. Compared with normal sleepers, unsedated critically ill patients spent little time in stable sleep (percent odds ratio product < 1.0: 31% vs 63%; p < 0.001), whereas most of the time were either in stage wake (odds ratio product > 1.75) or in a transitional state (odds ratio product 1.0–1.75), characterized by frequent wake intrusions. Propofol and dexmedetomidine had comparable effects on sleep. Sedation resulted in significant shift in odds ratio product distribution toward normal; percent odds ratio product less than 1.0 increased by 54% ( p = 0.006), and percent odds ratio product greater than 1.75 decreased by 48% ( p = 0.013). In six patients (26%), sedation failed to improve sleep. CONCLUSIONS: In stable critically ill unsedated patients, sleep quality is poor with frequent wake intrusions and little stable sleep. Light sedation with propofol or dexmedetomidine resulted in a shift in sleep architecture toward normal in most, but not all, patients.